2021
DOI: 10.3329/birdem.v12i1.57225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between online and traditional teaching-learning among non-clinical medical students

Abstract: Background: Medical institutes remained on complete shut down during the coronavirus disease of 2019 (COVID-19) pandemic while Information Technology (IT) bridged the teaching learning between the students and teachers. The study objectives were to determine the opportunities and obstacles of teaching learning process and overall effectiveness of online classes over traditional classes. Methods: A cross-sectional study was conducted from July 2020 to December 2020 between students and teachers of Khulna city M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Modern technology fortunately allowed a swift transition to online meetings and presentations due to COVID but it must be borne in mind that substantial portions of potential audiences may have barriers to moving online in this way, and this includes poor network connections, data affordability, and hardware limitations. [ 15 ] Indeed, it has been shown that students' responses depend on their proficiency in employing online tools and technical ability to access online events. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Modern technology fortunately allowed a swift transition to online meetings and presentations due to COVID but it must be borne in mind that substantial portions of potential audiences may have barriers to moving online in this way, and this includes poor network connections, data affordability, and hardware limitations. [ 15 ] Indeed, it has been shown that students' responses depend on their proficiency in employing online tools and technical ability to access online events. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%